Petroleum geology of Africa : new themes and developing technologies - Arthur, T. 1952-; MacGregor, D. S.; Cameron, N. R. (Geological Society, 2003)
This is a collection of papers on a range of topics related to the petroleum geology of Africa. The book provides essential reading for those requiring further insight into the origins of Africa's diverse petroleum systems and will be key to geologists involved in the exploration of oil and gas throughout Africa.
One CD-ROM in pocket attached to inside back cover.
Keywords: Petroleum -- Geology -- Africa.; elektronické knihy; electronic books